Hypothermia and Early Neonatal Mortality in Preterm Infants - Branco de Almeida, Maria Fernanda; Guinsburg, Ruth; Sancho, Guilherme Assis; Machado Rosa, Izilda Rodrigues; Lamy, Zeni Carvalho; Martinez, Francisco Eulogio; Vieira Cavalcante da Silva, Regina Paula Guimaraes; Lopes Ferrari, Ligia Silvana; Rugolo, Ligia Maria Suppo de Souza [UNESP]; Steffen Abdallah, Vania Olivetti; Silveira, Rita de Cassia (Elsevier B.V., 2014)
Objective To evaluate intervention practices associated with hypothermia at both 5 minutes after birth and at neonatal intensive care unit (NICU) admission and to determine whether hypothermia at NICU admission is associated with early neonatal death in preterm infants.Study design This prospective cohort included 1764 inborn neonates of 22-33 weeks without malformations admitted to 9 university NICUs from August 2010 through April 2012. All centers followed neonatal International Liaison Committee on Resuscitation recommendations for the stabilization and resuscitation in the delivery room (DR). Variables associated with hypothermia (axillary temperature <36.0 degrees C) 5 minutes after birth and at NICU admission, as well as those associated with early death, were analyzed by logistic regression.Results Hypothermia 5 minutes after birth and at NICU admission was noted in 44% and 51%, respectively, with 6% of early neonatal deaths. Adjusted for confounding variables, practices associated with hypothermia at 5 minutes after birth were DR temperature <25 degrees C (OR 2.13, 95% CI 1.67-2.28), maternal temperature at delivery <36.0 degrees C (OR 1.93, 95% CI 1.49-2.51), and use of plastic bag/wrap (OR 0.53, 95% CI 0.40-0.70). The variables associated with hypothermia at NICU admission were DR temperature <25 degrees C (OR 1.44, 95% CI 1.10-1.88), respiratory support with cold air in the DR (OR 1.40, 95% CI 1.03-1.88) and during transport to NICU (OR 1.51, 95% CI 1.08-2.13), and cap use (OR 0.55, 95% CI 0.39-0.78). Hypothermia at NICU admission increased the chance of early neonatal death by 1.64-fold (95% CI 1.03-2.61).Conclusion Simple interventions, such as maintaining DR temperature >25 degrees C, reducing maternal hypothermia prior to delivery, providing plastic bags/wraps and caps for the newly born infants, and using warm resuscitation gases, may decrease hypothermia at NICU admission and improve early neonatal survival.